The Severity of Internal Carotid Artery Stenosis is Associated with the Cyclin-Dependent Kinase Inhibitor 2A Gene Expression - Deser, Serkan Burc; Arslan, Caner; Arapi, Berk; Bayoglu, Burcu; Dagistanli, Fatma Kaya; Gode, Safa; Cengiz, Mujgan; Dirican, Ahmet (Journal of Atherosclerosis and Thrombosis, 2014)
Aim: The INK4b-ARF-INK4a locus in the chromosome 9p21 region is known to play an important role in the development of atherosclerosis. The INK4/ARF transcript p16INK4a inhibits the activity of the cyclin-dependent kinases CDK4/CDK6 and arrests cell-cycle progression. CDK inhibitors also regulate G1/S phase progression in vascular smooth muscle cells(VSMCs) and may modulate the early stages of atherosclerosis. Therefore, we aimed to study the expression of the INK4/ARF locus genes CDKN2A and CDKN2BAS in order to examine the p16INK4a protein expression and the level of cell proliferation in carotid plaques and saphenous tissue samples. Methods: A total of 50 patients(33 symptomatic subjects and 17 asymptomatic subjects) with carotid atherosclerosis CA) were studied. The CDKN2A and CDKN2BAS gene expression levels were determined using quantitative real-time polymerase chain reaction(qRT-PCR). All tissue sections were also analyzed for the p16INK4a and proliferating cell nuclear antigen(PCNA) protein expression using immunohistochemistry(IHC). Results: The CDKN2A gene expression was significantly higher in the carotid plaques than in the saphenous tissues(p=0.009), whereas no such differences were observed in the CDKN2BAS transcripts(p=0.157). The carotid plaque CDKN2A mRNA levels were higher in the symptomatic patients than in the asymptomatic patients(p=0.050); this finding was also associated with the severity of internal carotid artery(ICA) stenosis(p=0.034). The p16INK4a immune(＋) cell counts in the carotid plaques were higher in the symptomatic patients than in the asymptomatic patients (p=0.056), as was the cell proliferation index(p=0.001). Conclusions: An increased CDKN2A gene expression in carotid plaques may increase the severity of ICA stenosis, thus raising the risk of atherosclerosis and contributing to the development of symptoms. In addition, the p16INK4a expression is associated with carotid atherosclerosis in various patient subgroups.